Demystifying the nutritional and anti-nutritional genetic divergence of Pakistani chickpea (Cicer arietinum L.) genetic resource via multivariate approaches - Jameel, Saima; Hameed, Amjad; Shah, Tariq Mahmud; Coyne, Clarice J. (Frontiers in Nutrition, 2024)
Chickpea is a highly versatile functional food legume, that possesses the capacity to boost human health and have potential to alleviate malnutrition related deficiencies. To investigate whole seed-based nutritional and anti-nutritional composition, a set of 90 chickpea genotypes (66 desi, 24 kabuli) was collected from different research organizations in Pakistan. Significant variation (Tukey HSD test, P < 0.05) was perceived among genotypes for traits under investigation. The genotypes with maximum total soluble protein (34.92%), crude protein (30.13%), and reducing sugars (17.33 mg/g s. wt.) i.e., Punjab-2000 (desi), total free amino acid (3.34 g/100g DW) i.e., Wild Hybrid-15 (desi), albumins (227.67 mg/g s. wt.) i.e., Sheenghar-2000 (desi), globulins (720 g s. wt.) i.e., ICCV-96030 (desi), salt soluble proteins (200 mg/g s. wt.) i.e., ILWC-247 (desi), total soluble sugars (102.63 mg/g s. wt.) i.e., CM1051/11 (desi), non-reducing sugars (95.28 mg/g s. wt.) i.e., NIAB-CH2016 (desi), starch content (83.69 %) i.e., CH55/09 (kabuli), and the genotypes with least value of anti-nutritional factors glutelin (3.33 mg/g s. wt.) i.e., Wild Hybrid-9 (desi), hordein (1.38 mg/g s. wt.) i.e., Noor-2013 (kabuli), tannins (5425 uM/g s. wt.) i.e., Wild Hybrid-1(desi) and phytic acid (0.18 mg/g s. wt.) i.e., Bhakhar-2011 (desi), could be the promising genotypes to formulate health promoting plant-based food products. Data was also analyzed for Principle component analysis (PCA), correlation, and agglomerative hierarchical clustering. PC-1 revealed the highest contribution (20.83%) towards cumulative variability and maximum positive factor loading was delivered by total soluble sugars (0.85) followed by starch content (0.729). Genotypes were grouped into 3 distinct clusters based on high average values of traits under investigation. Cluster-I encompassed the genotypes with a high mean value of crude protein content, albumins, hordein, and glutelin, Cluster-II with a high mean value of total soluble protein, total soluble sugars, non-reducing sugars, globulins, salt soluble sugars, starch, and total free amino acids, while genotypes having high tannins, reducing sugars and phytic acid grouped in cluster-III. Identified desi and kabuli genotypes exhibiting superior seed quality traits and minimal anti-nutritional factors can be used in chickpea breeding programs aimed on improving seed nutritional quality in future breeding lines.